PENGARUH SUPERVISI AKADEMIK DAN PENDIDIKAN /PELATIHAN (DIKLAT) TERHADAP KOMPETENSI PEDAGOGIK GURU DI KECAMATAN SEMARANG SELATAN - Purwanto, Edi; Fironika Kusumadewi, Rida; Solikhun, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the fluctuations in teachers' pedagogical competence in managing learning. Pedagogical competence is crucial for teachers to understand student characteristics, design appropriate learning strategies, and create an active and conducive classroom atmosphere. This ability improves the quality of teaching, learning outcomes, and helps teachers facilitate the optimal development of student potential. Therefore, it is necessary to address various factors assumed to influence it, such as academic supervision and training. This study aims to determine the effect of academic supervision and training on the pedagogical competence of public elementary school teachers in South Semarang District. The sample in the study was 124 teachers. Data collection was through the distribution of a questionnaire with a Likert scale of 1-5. Data analysis included normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, and hypothesis testing, processed using SPSS version 23. The results showed that 1) There is a positive effect of academic supervision on the pedagogical competence of elementary school teachers in South Semarang District, as the P-value of the academic supervision variable is 0.000 (<0.05), thus the proposed hypothesis is accepted. 2) There is no positive effect of training on the pedagogical competence of elementary school teachers in South Semarang District, as the P-value of training is 0.675 (>0.05), thus the proposed hypothesis is rejected. 3) There is a positive effect of academic supervision and training on the pedagogical competence of elementary school teachers in South Semarang District, as the P-value is 0.007 (<0.05), thus the proposed hypothesis is accepted.